Identifikasi Tipe Pemukiman Karang Nabuan di Banjar Tinggan Desa Plaga Kecamatan Petang Kabupaten Badung - I MADE BAYU ARTHA; A.A GEDE DALEM SUDARSANA; IDA AYU MAYUN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2014)
ABSTRACT Settlement Type Identification Karang Nabuan at Banjar Tinggan, Plaga Village, Petang Subdistrict, Badung Regency Based on Tri Hita Karana concept will cause Tri Mandala concept in Balinese settlement pattern as an implementation of Tri Hita Karana concept which divided into Utama Mandala, Madya Mandala, and Nista Mandala. The division of space based on Tri Mandala is already compose an space pattern which classification based on function of each those space. Based on division of space Tri Mandala, the space of Utama Mandala purposed as holy space ( Merajan), the space of Madya Mandala purposed as a place of residence that composed of bale daja, bale dangin, bale delod, and bale dauh, whereas for the space of Nista Mandala forms a space that purposed as telajakkan. The purpose of this research is to identify the type of habitation in Banjar Tinggan,  Plaga village, Badung. This research specifically for identify the habitation pattern karang nabuan, specially the spatial pattern, hard scape and soft scape, and to indentify land pattern and land dimention the habitation of karang nabuan. The research been done at Banjar Tinggan, Plaga village, Petang district, Badung regency area. The collection of datas been done since October 2012 until march 2013. The sample been taken to get this research data using sampling proposive and the point of been choosing from the natives people at Banjar Tinggan. Bali is an island that full with culture which possess its own settlement pattern that different from other settlement pattern. The variety of culture in Bali is related to environmental or Balinese geographical condition that caused the variety of settlement pattern. Banjar Tinggan is one of settlement area that located at foot of Mangu Mountain (Puncak Mangu) which possess settlement pattern that called Karang nabuan. Settlement pattern in that area is different from settlement pattern in Bali generally. The differences evident to several landskap compiler elements comparable to other Balinese territory. Karang nabuan is an settlement pattern that possess uniqueness because possess space pattern that not restricted intactly from one house to another so that the houses there is inside be in one land (karang) although not relative. Karang nabuan come from syllable Karang and Nabuan that come from word bee (tabuan). Karang nabuan is house in a clustering manner that composed as a bee’s house. The system of settlement pattern in each house not restricted by penyengker or wall, formed based on side by side, mass building that framer natah karang nabuan only contents bale daja, bale dauh, bale dangin, kitchen and without bale delod so that space pattern of natah not restricted intacly. Key word: Settlement Type, Karang Nabuan